Immune related genes expression in juveniles of an invasive snail after challenged with Lipopolysaccharide - Y M Xiong; Z H Yan; J E Zhang; H Y Li (Invertebrate Survival Journal, 2017)
Invasion by Pomacea canaliculata is an increasing problem worldwide. Its rapid invasion and spread depends on the immune mechanism of efficient treatment of unfavorable factors and pathogenic microorganisms in the environment. Transcriptome technology is widely applied in studying the interaction of molluscs and pathogenic microorganisms and the development of disease. In this study, transcriptome technology is used to detect the expression of immune-related genes after the P. canaliculata juvenile snails were challenged with Lipopolysaccharide (LPS) for 48 h. A total of 402 immune-related differentially expressed genes(DEGs) were identified in comparison with the control. These DEGs involved in antigen recognition gene, immune stress and detoxification. The results showed that genes associated with detoxification metabolism were significantly up-regulated, such as cytochrome c oxidase, cytochrome b oxidase, NADH dehydrogenase, sterol 17-alpha-hydroxylase and cytochrome P450. These data will provide fundamental information for subsequent studies of the immune defense mechanisms against pathogens in the juvenile snail of P. canaliculata.